A comparison for ease of insertion and adequacy of ventilation between laryngeal tube suctioning (LTS) and airway management device (AMD) - Ramli, Wan Marzuki Wan (2006)
The purpose of the study is to assess whether the recently introduced modified version of the airway management device (AMD) is easy, reliable, and safe as claims by the manufacturer. We compared the use the airway management device (AMD) with the laryngeal tube suctioning (L TS) in spontaneously ventilating adult patient undergoing general anaesthesia. Ease of insertion, the effectiveness of ventilation and incidence of airway complication when using the tube for airway maintenance were evaluated between the two groups. A randomized single blinded prospective study was conducted involving a total of 80 patients premedicated, ASA I or II patients, aged 18 to 65 years and were divided into 2 groups either L TS or AMD as for airway management during elective surgery After a standardized induction of anaesthesia with intravenous fentanyl 1.5 mcg.kg-1 and intravenous propofol 2 mg.kg-1 , a size 3 or 4 LTS or AMD was inserted and the patients breathed spontaneously throughout the surgery with no muscle relaxant given. Anaesthesia was maintained with nitrous oxide, oxygen and isoflurane. The airway device was removed at the end of surgery with the patients fully awake. The ease of insertion (easy: require one attempt; difficult: require 2 or 3 attempts; or failed), the rate of successful insertion and the incidence of airway trauma were recorded. Episodes of airway manipulations and desaturation intraoperatively were also recorded. We were able to achieve a clear airway in 36 patients (90.0%) in the LTS group and in 38 patients (95%) in the AMD group. In the L TS group, the LTS was considered easy to insert in 25 patients, difficult in 11 patients, and it was easy in 33 patients, difficult in 5 patients in the AMD group. The ease of insertion and success rates of insertion between the two groups were not significantly different (p=O.l56 and 0.338 respectively). There was no significant difference in the incidence and severity of the postoperative airway complications between the two groups. Although, the incidence of airway manipulation and desaturation were higher in AMD compared to the LTS but it is not likely to be clinically relevant in this study. We conclude that L TS and AMD performed equally well in the ease of insertion and atraumatic to the airway.